Grammatical Cohesion in the Poem of Al-Aswad ibn Ya'far)The Rope Has Become a Tear from the Names) - Assi.Prof Ahmed Huwaidi Jawad (Journal of College of Education, 2025)
This research attempts to uncover the factors that connect linguistic and non-linguistic elements, and their impact on the text, which, in their entirety, support grammatical cohesion in Al-Aswad ibn Ya'far al-Nahshali's poem "The Rope Has Become One of the Names of the One Who Is Torn." It was studied according to the means of grammatical cohesion, which are the various types of reference found in the poem, such as pre- and post-referential, textual, and situational. I then moved on to connect, which was in the form of additional connection, remedial connection, temporal connection, conditional connection, connection by conjunction, connection by generalization after detail, connection by circumstance, connection by repetition, connection by substitution, connection by advancement and delay. I then studied deletion and its impact on grammatical cohesion, which is the deletion of the subject, the deletion of the agent, the deletion of the predicate (ka'anna), and the deletion of (rabb). I then concluded the research with the most important results.
Keywords: Cohesion, Poet, Harmony, Reference, Connection